Phase Transition in the 2D XY Model with 3-Fold Nematic Interactions - Huyen, Nguyen Thi; Linh, Luu Bich; Thu, Bui Thi Toan; Cuong, Nguyen Huu; Binh, Nguyen Vu Cam; Hien, Nguyen Thuy; Viet, Dao Xuan; Nui, Duong Xuan (VNU Journal of Science: Mathematics - Physics, 2022)
In this work the results of the study on a generalization of the XY model with an additional q -fold nematic-like term through Monte Carlo simulations in two dimensions (2D) have been presented. While the conventional 2D XY model has only integer vortexes, the generalized 2D XY model has both integer and non-integer 1/ q vortexes, making the phase diagram of the generalized 2D XY model is much richer than that of the conventional 2D XY model. Here, we located the phase transition between the disordered phase (P), the quasi-long-range order phase (F), and the nematic phase (N) for the case of q = 3. We provided the numerical evidence to clarify the N−F phase transition of either the first-ordered or second-ordered phase transition. The results showed that the N−F phase transition is the second-ordered, not the first-order phase transition.